Participatory definition of trait preferences for designing village breeding schemes for goats in harsh environments of Ethiopia - Dessie, Tadelle; Gebreyesus, G.; Mekuriaw, Getinet; Woldu, T.; Jembere, T.; Agaba, Morris; Okeyo Mwai, Ally (American Society of Animal Science, 2014)
There is critical need to improve productivity of indigenous goat breeds in order to sustain supply of food and income to communities living in harsher areas that are coming to relay more and more on the drought tolerant commodity; goats, due to changing climate. To this end, a community-based goat breeding project is being implemented in 5 zones of Ethiopia by ILRI and its partners. Designing of the breeding programs proceeded phenotypic and molecular characterization of the indigenous Ethiopian goat breeds. The characterization studies revealed that ample genetic diversity exists between and within the indigenous goat breeds pointing hug potential to tap for improving productivity amid a changing climate. Participatory definition of trait preferences was undertaken to pave the way for deriving economic weights of traits to develop selection indices.